2020
DOI: 10.1177/0305735620937780
|View full text |Cite
|
Sign up to set email alerts
|

Laying the foundations for lifelong family music practices through Music Early Learning Programs

Abstract: To lay the foundations for lifelong musical practices, parents need to feel confident using music as a part of their everyday parenting. Music Early Learning Programs (MELPs) can empower parents to use music by laying the foundations for family-based active music-making. Little is known about why parents attend, however, what their aspirations are for their child’s musical engagement now and in the future, or how attendance shapes the way they use music at home. This study investigated parental beliefs, aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Music is a candidate domain as a family leisure activity because it creates meaningful and sustainable links between generations (Mehr, 2014; Williams et al, 2015). Many parents recognize its potential to strengthen family bonding, and welcome support to realize musical interactions (Abad & Barrett, 2020). For example, Custodero, Rebello Britto, and Brooks-Gunn (2003) found that 60% of U.S. parents engaged musically with their infants, in which mothers took a greater part as compared to fathers.…”
Section: Introductionmentioning
confidence: 99%
“…Music is a candidate domain as a family leisure activity because it creates meaningful and sustainable links between generations (Mehr, 2014; Williams et al, 2015). Many parents recognize its potential to strengthen family bonding, and welcome support to realize musical interactions (Abad & Barrett, 2020). For example, Custodero, Rebello Britto, and Brooks-Gunn (2003) found that 60% of U.S. parents engaged musically with their infants, in which mothers took a greater part as compared to fathers.…”
Section: Introductionmentioning
confidence: 99%
“…Music groups and classes are a popular activity for parents with young children outside the home in Australia, the UK and the USA (Abad & Barrett, 2020;Pitt & Hargreaves, 2017;Rodriguez, 2019). Families report attending music groups and early childhood music programmes to support their child's development (Abad & Barrett, 2020) and musical development (Rodrigeuz, 2019), to facilitate their child's social interactions (Pitt & Hargreaves, 2017;Rodrigeuz, 2019), and to connect with other families as a means of social support (Abad & Barrett, 2020;Rodriguez, 2019). Additionally, attendance at a music group is reported to support music-making practices in the home (Abad & Barrett, 2020;Barrett, 2009;Pitt & Hargreaves, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of these therapeutic programmes is referred to as Music Early Learning Programs (MELPS). MELPS can empower parents to use music by laying the foundations for family-based active music making (Abad & Barrett, 2020). MELPS provide a framework for caregivers to engage in shared music activities with their child and support the child's social, emotional and musical development (Abad, 2018;Abad & Barrett, 2020).…”
Section: Music-making With Families Of Typically Developing Childrenmentioning
confidence: 99%